Microfluidics chips fabrication techniques comparison - Liu, Xiaocheng; Sun, Antao; Brodský, Jan; Gablech, Imrich; Lednický, Tomáš; Vopařilová, Petra; Zítka, Ondřej; Zeng, Wen; Neužil, Pavel (Scientific reports, 2024)
This study investigates various microfluidic chip fabrication techniques, highlighting their applicability and limitations in the context of urgent diagnostic needs showcased by the COVID-19 pandemic. Through a detailed examination of methods such as computer numerical control milling of a polymethyl methacrylate, soft lithography for polydimethylsiloxane-based devices, xurography for glass-glass chips, and micromachining-based silicon-glass chips, we analyze each technique's strengths and trade-offs. Hence, we discuss the fabrication complexity and chip thermal properties, such as heating and cooling rates, which are essential features of chip utilization for a polymerase chain reaction. Our comparative analysis reveals critical insights into material challenges, design flexibility, and cost-efficiency, aiming to guide the development of robust and reliable microfluidic devices for healthcare and research. This work underscores the importance of selecting appropriate fabrication methods to optimize device functionality, durability, and production efficiency.
Keywords: Polymethyl Methacrylate; dimethylpolysiloxany; Dimethylpolysiloxanes; Microfluidic Analytical Techniques; mikrofluidika; Lab-On-A-Chip Devices; polymethylmethakrylát; laboratoř na čipu; design vybavení; lidé; Microfluidics; mikrofluidní analytické techniky; Humans; Equipment Design; COVID-19; SARS-CoV-2